Modern Armenian drama : an anthology - Parlakian, Nishan, 1925-; Cowe, S. Peter (Columbia University Press, 2001)
Available in English for the first time, Modern Armenian Drama presents seven classic works from the Armenian stage. Spanning over a century (1871-1992), the plays explore such diverse themes science and religion, socioeconomic injustice, women's emancipation, and political reform through the medium of all the major European dramatic genres. Nishan Parlakian and S. Peter Cowe provide a comprehensive introduction to the history of Armenian drama, giving a valuable overview of its importance and development in Armenia, as well as a brief biography for each playwright. A preface to each play helps in placing the work within the context of historical and cultural issues of the time. Like the plays of Ibsen and O'Neill, the plays presented in this anthology are considered modern classics. They have an enduring quality and appeal to audiences who see them today. The editors have collected translations of the best examples of Armenian theater from its renaissance in the mid-nineteenth century to the present.